Central action of CART induces neuronal activation in the paraventricular and dorsomedial hypothalamus of diet-induced obese and lean mice. (1st November 2018) - Romeu, Deborah de Paula; Ribeiro, Luciene Maria; Antunes, Vagner Roberto
Highlights: The central action of CART selective activates the PVN and DMH of obese mice than of lean mice. CART is a putative link between the metabolic and cardiovascular dysfunction at the hypothalamus level in obesity state. The CART can be a key peptide at the CNS level involved in the development of obesity-induced hypertension. Abstract: The cocaine- and amphetamine-regulated transcript (CART) is a peptide commonly studied in the feeding behavior, but it exerts an important role in the autonomic and cardiovascular control as well. It is known that exogenous administration of CART in the central nervous system can elicit increase in blood pressure of both conscious and anesthetized rodents, but little is known whether these central effects might differ between lean and obese animals. We have recently shown that diet-induced obese mice that developed hypertension presented an upregulation of CART levels in the dorsomedial nucleus of hypothalamus, while obese normotensive ones had not. Herein we investigate whether the central action of CART could activate differently the hypothalamic nuclei of diet-induced obese mice compared to the lean counterparts by using Fos protein expression, C57BL/6 mice were randomly assigned to two cohorts, one fed with a high-fat diet for 8 weeks (obese), and the other fed with regular rodent chow (lean). Both groups received an ICV injection of CART at the dose of 400μM, 1 mM or vehicle. Subsequently, the brains were processed for Fos protein immunohistochemical in order to identify hypothalamic neuronal activation. Significantly greater numbers of Fos-positive neurons were observed in the PVN and DMH of obese mice that received CART 1 mM, when compared to the lean control. These results indicate that the central action of CART induces neuronal activation in the hypothalamic nuclei of obese and lean mice, and this could be relevant to the different autonomic and cardiovascular adjustments that an organism exposed to different diet and metabolic condition.